2018
DOI: 10.1293/tox.2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent acute toxicity of silver nanoparticles in mice

Abstract: In this study, we aimed to evaluate changes in the acute toxicity of intraperitoneally administered silver nanoparticles (AgNPs) of varying sizes in BALB/c mice. Seven-week-old female BALB/c mice were intraperitoneally administered AgNPs measuring 10, 60, or 100 nm in diameter (0.2 mg/mouse) and then sacrificed 1, 3, or 6 h after treatment. In mice administered 10 nm AgNPs, reduced activity and piloerection were observed at 5 h post administration, and lowered body temperature was observed at 6 h post administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 24 publications
5
73
0
Order By: Relevance
“…Ultrastructural examination of the lung of Ag-Nps exposed rats revealed pneumocytes type II with irregular heterochromatic nuclei and vacuolated cytoplasm with empty or irregular lamellar bodies. Vacuolated cytoplasm was also detected previously in hepatic cells of both rats and mice [78,79] .…”
Section: Discussionsupporting
confidence: 71%
“…Ultrastructural examination of the lung of Ag-Nps exposed rats revealed pneumocytes type II with irregular heterochromatic nuclei and vacuolated cytoplasm with empty or irregular lamellar bodies. Vacuolated cytoplasm was also detected previously in hepatic cells of both rats and mice [78,79] .…”
Section: Discussionsupporting
confidence: 71%
“…However, several studies have shown that AgNPs can be toxic for different cell lines finally leading to cell apoptosis and necrosis (Kaba & Egorova, 2015;Sambale et al, 2015). In fact, the cytotoxic and inhibitory effects of AgNPs on cells are highly dose, size, shape, and time dependent (Cho et al, 2018;Konop et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a review study reported that the common sizes of AgNPs used in general applications ranging from 1 to 10 nm [40]. The reason behind this is that smaller particles have been found to display better antimicrobial and cytotoxic activity, as demonstrated in various studies [38,41,42]. Furthermore, as the particle size gets smaller, the specific surface area increases and, hence, a greater proportion of its atoms is displayed on the surface [4] This implies that for the same mass of an NP, biological interactions and toxicity are more dependent on particle number and surface area than on particle mass.…”
Section: Agnps Physicochemical Propertiesmentioning
confidence: 98%
“…On the other hand, Boudreau M.D et al [36], using similar particles, showed the dose-dependent accumulation of AgNPs in various tissues of rats, without causing significant cytotoxicity. Moreover, some published nanotoxicity studies have reported characteristics of the particles by using only manufacturer's data without investigators to confirm their found characteristics or by using single analytical tool that provides limited information about the particle-type being studied [35,[37][38][39]. This brings in the importance of the adequate physicochemical characterization of AgNPs prior to undertaking toxicity assessment studies.…”
Section: Nanotechnologymentioning
confidence: 99%